2021
DOI: 10.1007/s11011-021-00774-9
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol promotes neurogenesis in the dentate gyrus during an abstinence period in rats following chronic exposure to methamphetamine

Abstract: Chronic methamphetamine (meth) abuse can lead to certain de cits in the hippocampal function by affecting the hippocampal neurogenesis and plasticity. To determine whether cannabidiol (CBD) can promote proliferation and maturation of neuronal progenitor cells, this study investigated the CBD effect on neurogenesis in the hippocampal dentate gyrus (DG) following chronic exposure to meth in rats. The rats received 2 mg/kg of meth twice a day for ten days. Next, immuno uorescence was performed to evaluate the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…As CBD promotes neurogenesis in the Hip of rats under chronic METH exposure ( Razavi et al, 2021 ) and modulates the psychoactive properties of METH via DA receptors in the Hip of rats ( Hassanlou et al, 2021 ; Nouri et al, 2021 ), we repeated the above experiments in the Hip. Results showed that METH exposure induced DRD1 [ Figure 11A ; F (3, 16) = 74.578, p < 0.001], pMeCP2 [ Figure 11A ; F (3, 16) = 63.564, p < 0.001], cleaved caspase-8 [ Figure 11A ; F (3, 20) = 44.202, p < 0.001], and cleaved caspase-3 expression [ Figure 11A ; F (3, 16) = 25.338, p < 0.001] in the Hip, whereas CBD pretreatment blocked the high expression of DRD1 [ Figure 11A ; F (3, 16) = 74.578, p < 0.001], pMeCP2 [ Figure 11A ; F (3, 16) = 63.564, p < 0.001], cleaved caspase-8 [ Figure 11A ; F (3, 20) = 44.202, p < 0.001], and cleaved caspase-3 [ Figure 11A ; F (3, 16) = 25.338, p < 0.001].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As CBD promotes neurogenesis in the Hip of rats under chronic METH exposure ( Razavi et al, 2021 ) and modulates the psychoactive properties of METH via DA receptors in the Hip of rats ( Hassanlou et al, 2021 ; Nouri et al, 2021 ), we repeated the above experiments in the Hip. Results showed that METH exposure induced DRD1 [ Figure 11A ; F (3, 16) = 74.578, p < 0.001], pMeCP2 [ Figure 11A ; F (3, 16) = 63.564, p < 0.001], cleaved caspase-8 [ Figure 11A ; F (3, 20) = 44.202, p < 0.001], and cleaved caspase-3 expression [ Figure 11A ; F (3, 16) = 25.338, p < 0.001] in the Hip, whereas CBD pretreatment blocked the high expression of DRD1 [ Figure 11A ; F (3, 16) = 74.578, p < 0.001], pMeCP2 [ Figure 11A ; F (3, 16) = 63.564, p < 0.001], cleaved caspase-8 [ Figure 11A ; F (3, 20) = 44.202, p < 0.001], and cleaved caspase-3 [ Figure 11A ; F (3, 16) = 25.338, p < 0.001].…”
Section: Resultsmentioning
confidence: 99%
“…CBD exhibits excellent therapeutic potential in neuropsychiatric disorders such as epilepsy, PD, AD, depression, anxiety, psychosis, and drug dependence ( Elsaid et al, 2019 ; Premoli et al, 2019 ; Vitale et al, 2021 ). Under METH exposure, CBD shows neuroprotective ( Razavi et al, 2021 ), antioxidative, and anti-inflammatory properties ( Majdi et al, 2019 ; Karimi-Haghighi et al, 2020 ). In addition, CBD can restore the adaptation to threshold doses caused by repeated METH exposure ( Khanegheini et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations